EFFECTS OF ANTIBIOTICS ON GUT MICROBIOTA - Norah Mohammed Sadly , Eman Al Humidi Al Enazi , Wafa Saeed Mohammed Al-Dosari , Khaled Khamis Al Khamis, Saad Saeed Al-Shahrani, Aisha Ayed Al-Omari , Amirah Ahmed Hussen Alhamali, Fatima Ahmed Alhamali, Turki Abdullah Aldahayan , ,; Ali Saad Mubarak Aldosari , Afaf Tirad Saud Alruwaili, Salman Salem Alharbi , 1osef Mohammed Alowaymer, Alshahrani, Khalid Munahi, Sultan Mansour Bin Dhuwayhi, (Chelonian Research Foundation, 2022)
The diversity of the human gut microbiota rapidly develops from birth until three years of age, when it reaches an adult-like stage. After this age, the composition could change as a result of outside influences such antibiotics. Prior research has demonstrated that resilience does not fully develop months after stopping antibiotic use. The short-term consequences of antibiotic consumption on the gut microbial ecology are, however, poorly understood. Here, we looked at the load and makeup of the fecal microbiota in 21 individuals who were treated with broad- spectrum antibiotics such β-lactams and fluoroquinolones right after treatment. For the purposes of microbial load and community composition investigations using quantitative PCR and pyrosequencing of the 16S rRNA gene, respectively, feces samples were taken from each participant one week after treatment and prior to treatment. The core phylogenetic microbiota shrank from 29 to 12 species, and microbial diversity was dramatically reduced by 25% as a result of fluoroquinolones and β-lactam antibiotics. On the other hand, these drugs raised the Bacteroidetes/Firmicutes ratio at the phylum level (p = 0.0007, FDR = 0.002). Our results unexpectedly showed that both antibiotic kinds raised the proportion of several unknown taxa that belong to the Gram-negative Bacteroides genus of bacteria at the species level (p = 0.0003, FDR<0.016). Moreover, the therapy had an impact on the mean microbial burden. In fact, it was considerably elevated by two times (p = 0.04) by the β-lactams. Key Words: Antibiotics, gut microbiota, broad-spectrum